Accident causation models developed in China between 1978 and 2018: Review and comparison. (April 2022) - Ge, Ji; Zhang, Yuyuan; Chen, Shoukun; Xu, Kaili; Yao, Xiwen; Li, Jishuo; Liu, Bo; Yan, Fang; Wu, Chunying; Li, Shuangyuan
Highlights: More than 21 accident causation models have been proposed in China over the past four decades. Trajectory Intersecting Model is the first accident causation model developed in China. There are three common characteristics in most of Chinese accident causation models. Five popular accident causation models developed in China are introduced and compared. These popular accident causation models have an important impact on government policy-making and accident investigation. Abstract: As the theoretical foundation of safety science, accident causation models provide a theoretical framework of accident analysis and prevention. Accident causation theories and models form the basis for many safety research fields and practices. There are many accident causation models proposed by safety researchers. However, accident causation models proposed by Chinese scholars are not known outside China, because most of these models have been published in Chinese. A brief history of accident causation models developed in China is presented according to the timeline in this article. The rapid development of safety science and its discipline in China began in 1978, which is the beginning year of Chinese Reform and Open-up. More than 21 different accident causation models have been proposed by safety researchers in China between 1978 and 2018. According to three criteria, these accident causation models are classified into two types: general accident models and popular accident models. Most accident causation models as general models have not been applied or known since they were proposed. Five popular accident causation models are selected to be introduced in some detail and compared with other models. To some extent, these accident causation models have influenced on the government policy formulation and accident investigation.